Europe and Africa The Long Search for Common Ground - Carbone, Giovanni (ISPI Publications, 2021)
A year and a half after the new Strategy with Africa proposed by the European Commission was made public, the new partnership between the two continents is still being defined. The impact of the Covid-19 pandemic with Africa's first economic recession in 25 years and a sharp rise in poverty and debt has created new challenges for the two continents' agenda, highlighting new gaps to address on the way forward. With the European Union-African Union summit scheduled for February 2022, the definition of the new partnership is once again gathering momentum, while both sides are still trying to define common positions. Will these two "natural partners" be able to tackle the most urgent challenges and turn them into opportunities for collaboration and engagement? What are the priority issues, and which ones are potentially most divisive?